Expert System For Determining Lecturer Performance Based On TRIDHARMA With Fuzzy Methods - Turaina, Rifa; Putri, Nency Extise (Jurnal Sains dan Informatika, 2016)
Performance of lecturer need to be measured and evaluated so that known weaknesses that occur in the execution of task and can see the description of the result that will be achieved in the future. Performance is rated based on lecturer tridharma college, if performance assessment of lecturers is done manually, this will be difficult and take a long time. Therefore it takes expert system that aims to determine the performance assessment of lecturers. Performance of lecturers will be judged on criteria tridharma college.